UNSUR GHARAR DALAM PEMBERIAN VOUCHER PROMO SHOPEE - Fadhiel, Zhul; Mariana, Mariana; Armia, Armia (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This research aims to understand the practice of giving promotional vouchers on the Shopee application and identify elements of gharar. The research method used is qualitative, by conducting field research using interviews, documentation and observation. The research results show that the practice of giving promo vouchers through the Shopee application is a program organized by Shopee.id. The mechanism of this program is simple, where Shopee application users who are interested in getting promo vouchers must participate in a prize draw or other promo. Users must fulfill the terms and conditions set by the organizer. These terms and conditions can be easily accessed via the Shopee application or the official Shopee website. However, gharar practices were found related to giving Shopee promotional vouchers among STIS Al-Hilal Sigli students. Some students experienced uncertainty where the vouchers were not provided as promised. For example, even though customers are supposed to get a 20% promotional voucher, the price of the item after the promo does not reflect the promised discount. For example, if the initial price of an item is IDR 10,000, it should be IDR 8,000 after the promo, but in reality this is not the case. This creates uncertainty and ambiguity regarding the benefits that users should obtain through providing promotional vouchers